Development Framework for Social Circle Relationship Learning Software for Children with Autism (Journal of Digital System Development, 2024)
Autism, also called Autism Spectrum Disorder (ASD), is a complex condition that includes problems with communication and behaviour. Due to the increasing awareness among parents, these children are increasing every year. The safety of children is a crucial subject in family life both inside and outside the home. All parents want the best for their children, especially when they are away from the family. Recognising this situation, an application proposal was developed to expose their level of security when meeting the people around them. The social circle relationship was first introduced as an aid for students with special needs to categorise the people they meet. This study implemented the social circle relationship as an application for an early-stage prototype to be tested on selected respondents. Five autistic children, with their parents as instructors, modified the prototype to suit their child. The built-in framework was used as a guide and reference for developing the application that fits this concept of social circle relationship. The study employed a mixed method, mainly implying a quantitative methodology to analyse the collected data. The effectiveness of the proposed framework was validated using two experts’ judgments and learners’ feedback through interviews and experimental evaluation, respectively. The results indicated that the proposed framework effectively taught social boundaries and provided autistic children with satisfaction.